Report from Paris. The German Military Attaché in France, Detlof von Winterfeldt, and his views of the French Army, 1909–1914. (November 2019) - Grawe, Lukas
Although historiography often attributes the German military leadership a high responsibility for the outbreak of the First World War, the action of the German military attaché in Paris, Detlof von Winterfeldt, has so far been ignored. This article shows how Winterfeldt assessed the strengths and weaknesses of the French army and describes how his reporting influenced the General Staff's evaluations in Berlin. It examines the concrete effects of his reporting on German military policies and military planning before 1914 to ascertain whether the General Staff relied on Winterfeldt's reports and if so, what difference they made.